MiRNA Regulation of MIF in SLE and Attenuation of Murine Lupus Nephritis With miR-654 - Tu, Yang; Guo, Ruru; Li, Jia; Wang, Suli; Leng, Lin; Deng, Jun; Bucala, Richard; Lu, Liangjing (Frontiers in Immunology, 2019)
Objective. Macrophage Migration Inhibitory Factor (MIF) is involved in the pathogenesis of systemic lupus erythematosus (SLE) and lupus nephritis(LN). MicroRNAs (miRNAs) play important roles in LN but whether specific miRNAs regulate the expression of MIF in LN is unknown. We explore specific miRNAs that can regulate MIF expression, and investigate miR-654 for the treatment of experimentally-induced murine lupus nephritis. Methods. Sera samples from 24 SLE patients and 24 controls were collected to measure MIF level, and its correlation with disease activity. Luciferase reporter assay was used to explore the target of miR-654. ELISA was used to detect the downstream cytokines regulated by miR-654 and MIF. Western blot was applied to measure the impact of miR-654 inhibition on downstream MIF signaling. The therapeutic efficacy of miR-654 was tested in the pristine induced lupus mouse model. We further measured miR-654 expression and analyzed its relationship with MIF expression in SLE patients. Results. Serum MIF level was increased in SLE patients (p<0. 001), positively correlated to SLEDAI score (r=0. 6348; p=0. 0009). MiR-654 inhibited MIF and downstream inflammatory cytokine production by selectively inhibiting the phosphorylation of ERK and AKT. Activation of miR-654 reduced IL-1β, IL-6, IL-8 and TNF-α production, relieved glomerulonephritis, and decreased MIF, IgG, and C3 expressions in murine lupus glomeruli. Furthermore, MIF was negatively correlated with miR-654 expression (r=-0. 5787; p=0. 0031) in SLE patients. Conclusion. MiR-654 negatively correlated with MIF and disease activity in patients with SLE. MiR-654 inhibits MIF expression via binding to MIF 3’UTR, selectively suppresses the phosphorylation of ERK and AKT, and reduces downstream inflammatory cytokine production. In vivo miR-654 treatment decreases MIF and downstream cytokine production and ameliorates murine lupus nephritis.